Production and Quality Evaluation of Cupcakes Enriched with Prebiotics - Hanan, A. Hussien; Hayat, M. N. Afify; Zeinab, A. Shabib (Food Technology Research Journal, 2023)
This study aimed to assess the physicochemical and sensory properties of cupcakes enriched with sugar beet pulp powder and potato peel powder. Potato peels had the highest protein (12.20%) and fat (2.25%), followed by wheat flour at 11.73 and 1.08% and sugar beet pulp at 10.50 and 0.35%. Crude fiber but soluble dietary fiber were highest in sugar beet pulp powder, while total dietary fiber and insoluble dietary fiber were the highest in potato peel powder, while wheat flour (72% extraction) had the lowest values. The substitution in cupcakes resulted in a decrease in fat content, an increase in ash content, and a significant increase in crude fiber and total dietary fiber contents, as well as soluble and insoluble fiber contents, compared with the control. The physical properties showed an increase in the hardness of cupcakes, and a negative correlation was found between specific volume and hardness. The findings suggest that the crust and crumb color of the produced cupcakes varied with the quantity of fiber used. The sensory evaluation showed that the addition of sugar beet pulp and potato peel powder up to 15% resulted in expectable cupcakes.